(untitled) (LACCEI, 2024)
The present study determined the physical-spatialarchitectural quality in the work performance of employees of the municipality of Chilete, to make architectural design decisions. Method: The inductive, deductive method was used to analyze and describe the different case studies based on two Municipalities: Chugay district and Virú province. This study identified four firstlevel categories and forty-three second-level indicators in four dimensions: functional design (layout and area), flow organization, support facilities, and environmental details (physical and landscape environment) were used. Results: The study showed that the main parameters that were developed for the integral design and functional flexibility comply with 88.23% in high adaptability. In the optimization of flows where 84.375% meets high adaptability to the flows of circulation and evacuation of the municipal infrastructure. Conclusion: Optimize the design of the waiting space in pediatric clinics, with a focus on functional design, flow organization, facilities, support, and environmental details, improving general satisfaction in the waiting environments and offices of the institution. The results are preliminary they need to be further tested in reality by completing the evaluation process based on the case studies. Guiding us with alternatives to sift the integral design of the spatial physical quality that will be used by municipal employees.